Sociodemographic Overview of Scabies Patients at the Pamenang Clinic, Jambi, Indonesia - Ulva, Maria; Yenti Sukarida; Lukman Setiadi; Mery Lisa Pratiwi (HM Publisher, 2024)
The Pamenang Clinic in Jambi Province, Indonesia, is a health service facility that plays an important role in providing care to patients suffering from scabies. In this context, it is very important to understand the sociodemographic features of patients who come to this clinic with complaints of scabies. Sociodemography includes various aspects such as age, gender, social status, and geography that contribute to patient characteristics. This study presents a sociodemographic overview of scabies patients at the Pamenang Clinic, Jambi, Indonesia as a scientific basis and reference for studies related to scabies. This study is descriptive observational research and uses secondary data. A total of 122 research subjects took part in this study. In conclusion, the majority of scabies patients at the Pamenang Clinic, Jambi, Indonesia, were aged between 6-19 years. Meanwhile, the average age is 22.6±2.7. The majority of research subjects were male, totaling 70 people.